2017
DOI: 10.1111/biom.12812
|View full text |Cite
|
Sign up to set email alerts
|

Covariate-adjusted Spearman's Rank Correlation with Probability-scale Residuals

Abstract: Summary It is desirable to adjust Spearman’s rank correlation for covariates, yet existing approaches have limitations. For example, the traditionally defined partial Spearman’s correlation does not have a sensible population parameter, and the conditional Spearman’s correlation defined with copulas cannot be easily generalized to discrete variables. We define population parameters for both partial and conditional Spearman’s correlation through concordance-discordance probabilities. The definitions are natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 32 publications
(61 reference statements)
1
72
0
Order By: Relevance
“…But there still exists a problem that the result is not stable enough. As for the stability, three indices, Pearson's correlation coefficient [35], Spearman's rank correlation coefficient [36], and Tanimoto distance [37], are commonly used to assess the performance of stability thoroughly in recent years. In the future, further research will focus on the stability of csFs to obtain a better performance from the perspective of three indices.…”
Section: Resultsmentioning
confidence: 99%
“…But there still exists a problem that the result is not stable enough. As for the stability, three indices, Pearson's correlation coefficient [35], Spearman's rank correlation coefficient [36], and Tanimoto distance [37], are commonly used to assess the performance of stability thoroughly in recent years. In the future, further research will focus on the stability of csFs to obtain a better performance from the perspective of three indices.…”
Section: Resultsmentioning
confidence: 99%
“…In practice, we have used orm, introduced in Section 3.2, to obtain maximum likelihood estimates based on the semiparametric transformation model. Extensive simulations have shown that Spearman's partial correlation using PSRs performs remarkably well with orm, even when models are misspecified (e.g., orm with a cloglog, instead of probit, link is fit to normal data) (Liu et al, 2017).…”
Section: Spearman's Partial and Conditional Rank Correlationsmentioning
confidence: 99%
“…If Z is categorical, then this correlation can simply be calculated in each level of Z. With continuous Z, the conditional rank correlation can be computed either nonparametrically with, for example, kernal smoothers, or modeled with parametric functions (Liu et al, 2017).…”
Section: Spearman's Partial and Conditional Rank Correlationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach results in a covariate-adjusted partial Spearman’s rank correlation between X and Y that incorporates the order information of these variables but does not assign arbitrary numbers to the categories; the null hypothesis of conditional independence can be tested. Some additional work has considered other outcome types (Liu et al, 2016; Shepherd et al, 2016). …”
Section: Some Simple Examples With a Single Ordinal Predictormentioning
confidence: 99%